2021
DOI: 10.1007/s12144-021-01551-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of body image dissatisfaction among youth in the United Arab Emirates: gender, age, and body mass index differences

Abstract: The term body image dissatisfaction (BID) describes the negative perceptions that a person carries about his or her own body. This study aimed to determine the prevalence of BID among youth in the UAE and how it is affected by three variables: sex, age, and body mass index (BMI). Participants were 728 UAE federal university students who responded to the Body Shape Questionnaire. Results indicated that 36.7% of students are dissatisfied with their body image. Gender differences analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 75 publications
1
18
1
2
Order By: Relevance
“…A recent study conducted among university students in the United Arab Emirates identified gender differences in the perception of body image where significantly more females desired a thinner body while males desired a heavier body [ 20 ]. However, a shift in gender disparities of body image dissatisfaction has been observed in the region where young men showed higher levels of body image dissatisfaction than women [ 21 ]. It is therefore important to study this pattern in the Omani context and investigate if this shift in body image perception is a new persistent trend.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted among university students in the United Arab Emirates identified gender differences in the perception of body image where significantly more females desired a thinner body while males desired a heavier body [ 20 ]. However, a shift in gender disparities of body image dissatisfaction has been observed in the region where young men showed higher levels of body image dissatisfaction than women [ 21 ]. It is therefore important to study this pattern in the Omani context and investigate if this shift in body image perception is a new persistent trend.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, men are more satisfied with their bodies than women, despite their physically larger size 15 . The opposite result was found in a study of university students in the United Arab Emirates, where men have higher levels of body image dissatisfaction 7 .…”
Section: Resultsmentioning
confidence: 80%
“…Individuals' negative perceptions have developed into a source of concern, particularly when experienced by children or teenagers 6 . Body image dissatisfaction (BID) refers to a person's negative perceptions of his or her own body 7 . Individuals with a negative body image will have a distorted perception of their physical appearance, causing them to feel ashamed of their own bodies 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This was also seen in Saudi women, where those with higher BMI had a signi cantly higher level of body image dissatisfaction (Albawardi et al, 2021;Aljadani, 2019). Likewise, Emirati studies reported that higher BMI was signi cantly related to higher body dissatisfaction for both women and men (Alharballeh & Dodeen, 2021;Radwan et al, 2019). Moreover, body satisfaction was signi cantly negatively correlated with BMI (r = .034, P-value < .001).…”
Section: Body Image and Bmimentioning
confidence: 87%